If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + 2) + 6 = 0 Reorder the terms: 4(2 + x) + 6 = 0 (2 * 4 + x * 4) + 6 = 0 (8 + 4x) + 6 = 0 Reorder the terms: 8 + 6 + 4x = 0 Combine like terms: 8 + 6 = 14 14 + 4x = 0 Solving 14 + 4x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + 4x = 0 + -14 Combine like terms: 14 + -14 = 0 0 + 4x = 0 + -14 4x = 0 + -14 Combine like terms: 0 + -14 = -14 4x = -14 Divide each side by '4'. x = -3.5 Simplifying x = -3.5
| 12-5*x=-33 | | -11.6h+11.55=-12.7h | | -9.1c+19.02=-14.3c+11.74 | | 21x-8=5(4x+5)-17 | | -5(r+2)=81 | | -1/2q-4=9 | | 20+4y=40 | | 5(10-2n)=70 | | 8(x+15)=7 | | 1/5q-49 | | 6(2g-1)=13 | | 4(g+4)=2(4-g) | | 4x+4=7y | | 4y+4=7y | | 1/3x10=55 | | -4(3x-7)=-12x-28 | | 5x+15=3(x+5) | | 112x=245x+95 | | 5.5=7.9-0.6x | | x-41=70 | | 7=-x+264 | | y+51=89 | | -37-8= | | h(t)=-16t^2+20t+17 | | x(x+3)-5=3x+20 | | 3x+7-5(x+1)=2x+5 | | 5y+3y-5=6(4y+3) | | -4s+9=-24 | | 2r+4=-16 | | (6+9)x=15x | | 10z^2+17z-20= | | 8y-12y+9=24-y |